2018
DOI: 10.1002/jbio.201700377
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet radiation oxidative stress affects eye health

Abstract: In the eye, ultraviolet radiation (UVR) is not known to contribute to visual perception but to mainly damage multiple structures. UVR carries higher energy than visible light and high dose exposure to UVR causes direct cellular damage, which has an important role in the development of cancer. This review provides an overview on the most recent knowledge on the role of UVR in oxidative stress (OS) in relation to noncancer ocular pathologies: various corneal pathologies, cataract, glaucoma and age-related macula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
147
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(158 citation statements)
references
References 92 publications
(142 reference statements)
2
147
0
9
Order By: Relevance
“…The photons present in UVB are directly absorbed by DNA; UVB not only can cause direct mutagenic and cytotoxic damage in cells, but it also induces the production of ROS, which indirectly damages DNA 11‐13 . Although negligible amounts of UVB reach the retina in adults, 14,15 we have utilized it in our experimental model in order to mimic a DNA‐damaged environment in human retinal pigment epithelium (RPE) cells. Although it is known that RPE is vulnerable to DNA damage during aging, it is still unresolved whether or not the NLRP3 inflammasome becomes activated in human RPE cells under these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The photons present in UVB are directly absorbed by DNA; UVB not only can cause direct mutagenic and cytotoxic damage in cells, but it also induces the production of ROS, which indirectly damages DNA 11‐13 . Although negligible amounts of UVB reach the retina in adults, 14,15 we have utilized it in our experimental model in order to mimic a DNA‐damaged environment in human retinal pigment epithelium (RPE) cells. Although it is known that RPE is vulnerable to DNA damage during aging, it is still unresolved whether or not the NLRP3 inflammasome becomes activated in human RPE cells under these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Our study has also suggested that the AF increases are originated from UV-induced, cysteine proteasemediated keratin 1 degradation. Because oxidative stress plays critical roles in UVinduced skin damage (4,9), it is necessary to elucidate the roles of the UV-induced AF increases and keratin 1 proteolysis. Our current study has suggested that oxidative stress mediates the UV-induced AF increases and keratin 1 proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress plays critical roles in UV-induced skin damage (4,9). A key question regarding our finding of UV-induced keratin 1 proteolysis is: Does oxidative stress play significant role in the UV-induced keratin 1 proteolysis?…”
Section: Introductionmentioning
confidence: 98%
“…Numerous epidemiological and experimental results have demonstrated that ultraviolet (UV) radiation in sunlight is the main cause of skin cancer and ocular disease, such as AMD [13][14][15][16]. Although the cornea and the lens of the eye substantially filter and attenuate UV radiation that enters the eyes, there is still a considerable amount of UV ray transmission to the retina.…”
Section: Introductionmentioning
confidence: 99%
“…The death and dysfunction of the RPE are closely associated with the pathogenesis of AMD [19], and the early and crucial event in AMD is impairment of the RPE [20]. Oxidative stress produced by UV radiation is a major factor associated with AMD, because oxidative stress not only leads to RPE cell damage and death [13,21] but also can cause protein misfolding and accumulation of lipid/protein aggregates in AMD [22].…”
Section: Introductionmentioning
confidence: 99%